Family Experiences of Patients with Diabetes Mellitus in Southeast and South - Natsir, Syamsul Alam; Syahrul, Syahrul (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting is a nutritional issue caused by prolonged insufficient nutrient intake, resulting in growth impairment in children, characterized by shorter height than the standard for their age. The causes of stunting are multidimensional, and one of them is food insecurity. Food insecurity is a condition where food needs are not adequately met at the regional, community, or household levels. According to data from the North Lombok District Health Office, there is a prevalence of 33.8% stunted toddlers in North Lombok District. Objective: This research aims to determine the relationship between food insecurity at the village level and the occurrence of stunting in children aged 24-59 months. Method: This study employed a cross-sectional study design with a total of 350 respondents selected using systemic random sampling method. Data on food insecurity were obtained from the North Lombok District Food Security Agency, while nutritional status data were obtained by measuring the length or height of toddlers using microtoice and infantometer, which were then compared with their age. The statistical test utilized in this study was the Chi-Square test.Results: The test on the relationship between food insecurity at the village level and the occurrence of stunting yielded a p-value of < 0.001, OR = <0.001, 95% CI = 0.086-0.225..Conclusions There is a significant association between food insecurity at the village level and the occurrence of stunting among toddlers aged 24-59 months.